CATALYSTS OF NEGOTIATION INITIATION IN EDUCATIONAL SETTINGS: AN EXPLORATION OF GENDER DYNAMICS - Allo, Markus Deli Girik; R, Meliati Banne; Sendana, Aris Kaban (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2024)
The objective of the study are to investigate the negotiation style uses by Man and Women and the gender influence on the initiation of negotiation in educational conversation context. The research design used in this study is a qualitative descriptive research design. The researchers used the purposive sampling technique to select participants. Participant of this research were an 11 male students and 11 female students of English students of UKI Toraja. The instrument used are observation and interview. This study used the interactive model to analyze data. Data analysis techniques are carried out interactively and take place continuously until complete until the data is saturated. This study confirms that: 1) both male and female participants exhibit a prevalent utilization of the 'compete' negotiation style when initiating conversations within diverse social contexts. Specifically, this negotiation style encompasses proactive engagement in discussions for the explicit purpose of seeking information pertinent to the context. Notably, a higher proclivity for information-seeking through competing behavior is observed among female participants, while male participants tend to engage in conversations without introducing novel topics, emphasizing the nature of their engagement as oriented toward interaction rather than information acquisition. 2) The Influence of Gender Initiation within the Educational Conversation Context, Particularly in the Realms of Attaining Research Information: A Scholarly Exploration and Fostering Collaborative Engagement for Assignment Completion among Peers.